Malaysian Teachers Thinking in History of Islam in Madina: A Qualitative Research - DAHALAN, SHAKILA; YUSOF, NAJEEMAH; ZAKARIA, ZUNAIDA (The journal of contemporary issues in business and government, 2021)
This article is to explores the teaching and learning history teachers in Malaysia. The article being a qualitative case study uses two data collecting approach namely observation and in-depth interview to collect data. Specifically, this article will explore integration of the Historical Thinking Skills (HTS) performed among history teachers in Malaysia who were selected using purposive sampling. First objective of this article are to identify the categories of Historical Thinking Skills (HTS) integrated by pre-service teachers. The other objectives of this article are to find out the categories of Historical Thinking Skills (HTS) often integrated by history teachers in Malaysia. A qualitative analysis showed that all four teachers focused on these two skills: discovering historical evidences and making interpretations. Out of the four participants, only one teacher focused on four skills during the observed lesson: discovering historical evidence, making interpretations, imagination and rationalizing facts in the lesson. This study provides an overall picture of the integration of the HTS by four selected teachers who emphasized on certain skills in their lessons. The implication of this study indicated that different teaching techniques were used by history teacher to facilitate the integration of various HTS in the teaching learning processes. Conclusion, the article provides a picture of the implementation of HTS in Malaysia and suggestions for integration thinking skills like historical thinking skills are offered.